Demethylzeylasteral (ZST93) inhibits cell growth and enhances cell chemosensitivity to gemcitabine in human pancreatic cancer cells via apoptotic and autophagic pathways. Issue 9 (4th January 2018) - Wang, Feng; Tian, Xiaodong; Zhang, Zhengkui; Ma, Yongsu; Xie, Xuehai; Liang, Jian; Yang, Chunxin; Yang, Yinmo
Abstract : The overall 5‐year survival rate of patients with human pancreatic cancer remains less than 8% because of its aggressive growth, early metastasis and resistance to conventional chemoradiotherapy. It is essential to develop innovative and effective therapeutic agents to improve its prognosis. Demethylzeylasteral (ZST93) is a novel triterpenoid monomer extracted from the xylem of Tripterygium roots. Our study aimed to assess the effects of ZST93 on cell proliferation and its role in the chemosensitivity to gemcitabine in human pancreatic cancer cells. The effects of ZST93 on cancer cell proliferation, cell cycle distribution, apoptosis and autophagy were evaluated in various human pancreatic cancer cell lines, and the antitumor effects of ZST93 alone and in combination with gemcitabine were identified in a xenograft mouse model. The results showed that ZST93 could inhibit the proliferation of pancreatic cancer cells and arrest cell cycle at G0/G1 phase by regulating the expression of Cyclin D1 and Cyclin A2. Moreover, ZST93 killed pancreatic cancer cells through two different mechanisms: inducing autophagic cell death at low concentrations and apoptotic cell death at high concentrations. Furthermore, ZST93 could enhance the chemosensitivity of pancreatic cancer cells to gemcitabine both in vitro and in vivo through modulation of the cross talk between autophagy and apoptosis. ZST93 is a potential therapeutic agent for developing novel therapeutic strategies in human pancreatic cancer. Abstract : What's new? Pancreatic cancer is an aggressive disease, marked by early metastasis, resistance to chemoradiotherapy, and low survival rates. Moreover, response rates to existing chemotherapeutic agents are poor, necessitating the development of new therapies. In this study, demethylzeylasteral (ZST93), a compound isolated from the plant Tripterygium wilfordii, was investigated for its effects on human pancreatic cancer cell lines and xenograft tumors in mice. Both in vitro and in vivo, ZST93 inhibited cancer cell proliferation and increased sensitivity to gemcitabine. Enhanced gemcitabine chemosensitivity in human pancreatic cancer cells was associated with excessive ZST93‐induced autophagic or apoptotic cell death.